2012
DOI: 10.1186/1471-2458-12-260
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pesticide suicide on the geographic distribution of suicide in Taiwan: a spatial analysis

Abstract: BackgroundPesticide self-poisoning is the most commonly used suicide method worldwide, but few studies have investigated the national epidemiology of pesticide suicide in countries where it is a major public health problem. This study aims to investigate geographic variations in pesticide suicide and their impact on the spatial distribution of suicide in Taiwan.MethodsSmoothed standardized mortality ratios for pesticide suicide (2002-2009) were mapped across Taiwan's 358 districts (median population aged 15 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 33 publications
5
38
1
3
Order By: Relevance
“…The identification of the profile of the SA could contribute to strategic planning that would make possible the prevention of the use of certain SA methods or help to design plans of care for subjects who have used methods. Several studies have reported which are the more commonly used means of SA [11][12][13] . The ingestion of medication, hanging and the use of cutting objects in SAs must be taken into consideration in the planning of care for the studied population.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of the profile of the SA could contribute to strategic planning that would make possible the prevention of the use of certain SA methods or help to design plans of care for subjects who have used methods. Several studies have reported which are the more commonly used means of SA [11][12][13] . The ingestion of medication, hanging and the use of cutting objects in SAs must be taken into consideration in the planning of care for the studied population.…”
Section: Discussionmentioning
confidence: 99%
“…En Colombia, se ha informado que las tendencias en las tasas de mortalidad por suicidios en hombres mostraron tasas específicas más elevadas en los grupos de 20 a 29 años de edad, entre 1985 y 2002 (47). Además, teniendo en cuenta que esas tasas fueron más altas en el área rural, los resultados parecen indicar una relación directa entre las labores agrícolas y la exposición a plaguicidas, como lo informaron Chang, et al, quienes encontraron que en las áreas con mayor proporción de personas ocupadas en actividades agrícolas, se reportaban las tasas más altas de mortalidad por intoxicación con plaguicidas autoinfligida intencionalmente (39).…”
Section: Discussionunclassified
“…Nevertheless, the frequency of common methods in terms of gender were low in some cities; therefore, the most common methods of suicide (self-immolation, use of drugs, and hanging) and suicide attempts (use of drugs, pesticide poisoning, use of cold weapons) were generally determined at the provincial level, and then, in the 27 cities of the province. Then, for each of the three common methods of suicide and suicide attempts, raw standardized mortality ratio (SMR) was calculated using indirect method based on the following formula: SMR = The number of observed cases/The number of expected cases The number of expected cases was calculated using the following formula (12): The number of expected cases = (The number of cases in the province/Population of the province) × The population of the city In order to calculate the rate of suicide and suicide attempts, the demographics information of the 2012 census was used (13). Due to the small population and reduced incidence of suicide in some cities and also to show a clear spatial pattern of suicide and suicide attempt before mapping (14), Bayesian hierarchical models and smoothed SMR (12) were calculated to separate the common methods of suicide and suicide attempts.…”
Section: Methodsmentioning
confidence: 99%
“…Then, for each of the three common methods of suicide and suicide attempts, raw standardized mortality ratio (SMR) was calculated using indirect method based on the following formula: SMR = The number of observed cases/The number of expected cases The number of expected cases was calculated using the following formula (12): The number of expected cases = (The number of cases in the province/Population of the province) × The population of the city In order to calculate the rate of suicide and suicide attempts, the demographics information of the 2012 census was used (13). Due to the small population and reduced incidence of suicide in some cities and also to show a clear spatial pattern of suicide and suicide attempt before mapping (14), Bayesian hierarchical models and smoothed SMR (12) were calculated to separate the common methods of suicide and suicide attempts. The Bayesian hierarchical models for observed cases of suicide were based on the Poisson assumption which allows the possibility of random effects for nonstructural diversity (heterogeneity in all regions of the area under consideration) and structural variation (the correlation between neighboring areas) (14,15).…”
Section: Methodsmentioning
confidence: 99%